Organizational Aspects of Realization of Ecological Education in the Educational Process of Preschool Establishments of Ukraine in 1990-s - Kravets, Nadiya (Pedagogical Discourse, 2012)
The article analyzes the scientists’ views to the problem of organization ecological education in preschool institutions in Ukraine in 1990-s. Also the article exposes the essence of the concepts «experience», «experiment», «research activity».